Observations of Autumnal Cooling in a Large Estuary. Issue 2 (8th February 2023) - Ilia, Amin; McCardell, Grant; Howard‐Strobel, Mary; O'Donnell, James
Abstract: Seasonal variations in solar insolation and wind create an annual water temperature cycle that impacts circulation and biological processes. The waters of Long Island Sound (LIS) warm from March‐February until August‐October and then begin to cool. Ship surveys show that the vertical temperature structure becomes almost uniform during this season when the area experiences low air temperatures and high winds. However, no observations have resolved the temporal evolution of the vertical structure of temperature during these cooling periods because conditions inhibit ship operations. We report glider measurements of the vertical structure of water temperatures and salinities from 22 October to 4 November 2014, in eastern LIS. We find that 20 m of water can cool at approximately 0.5 o C / d a y ${0.5}^{\mathrm{o}}\, \mathrm{C}/\mathrm{d}\mathrm{a}\mathrm{y}$ during intervals of cold air and strong winds. We use the data to estimate heat content tendencies and infer surface fluxes. We also estimate the surface heat fluxes using buoy‐mounted instruments and show they are consistent. The net heat flux to the atmosphere exceeds 600 W/m 2 during the gilder deployment and approximately 66% of this is due to latent heat transfer. Using the buoy fluxes and products of an operation regional model, we show that the agreement with the fluxes derived from heat budget is improved by using local wind observations. In addition to confirming the extremely large cooling rates, our results demonstrate that gliders can be used in a complex region with strong tidal currents to resolve the temperature structure and heat budget during the severe weather of the cooling season. Plain Language Summary: Long Island Sound is a large estuary surrounded by Connecticut and Long Island, NY. Seasonal variation in solar light and wind intensity results in water temperature differences in the sound. Surface water in LIS cools and sinks during fall. Mixing due to thermal convection and wind creates an almost uniform vertical temperature structure in the Sound. Due to the harsh weather during cooling events, ship operations are dangerous, so we used an automated underwater glider to observe this cooling process. After careful data sorting, the recorded temperatures were utilized to estimate the amount of heat loss from the Sound. These estimates were shown to be consistent with those calculated obtained using instruments on moored buoys. We also show that wind speed varies along the Sound, and has a subtle but significant role in the rate of surface cooling. Key Points: Rapid fall cooling in Long Island Sound (LIS) leads to vertical mixing and is caused by extremely large negative latent and sensible heat fluxes Wind speed has significant role in cooling and its spatial variations lead to slight differences in sensible and latent heat fluxes The heat fluxes from the Northeast Coastal Ocean Forecast System are consistent with the change in the heat content of eastern LIS